Dystopias and Historiographical Objects: The Strange Case of The Middle Ages - Riccardo Fedriga (Rivista di Estetica, 2021)
The article offers a critical reflection on the distance that separates us from an objectification of memory, its historiographical reconstructions and their different targets. At the basis of this enterprise, lies the belief that grasping the nuances and unveiling the ideological mechanisms of narrative reconstructions amounts to critically reflecting on the conditions that enable the narrative objectifications of the past filtered through by memory. To verify this theoretical assumption, the article elaborates on two key research tools that Umberto Eco has employed throughout his life and that permeated his overall work, i.e. the categories of use and interpretation, and applies them to the treatment of the Middle Ages as a historiographical object, to show how medievalism can be an interpretive tool that allows understanding the contemporary age and its hermeneutic and ideological distortions, its fears, its media representations.